Stable Transgenic Mouse Strain with Enhanced Photoactivatable Cre Recombinase for Spatiotemporal Genome Manipulation. Issue 34 (20th October 2022) - Li, Huiying; Wu, Yingyin; Qiu, Yuhao; Li, Xinru; Guan, Yuting; Cao, Xiya; Liu, Meizhen; Zhang, Dan; Huang, Sijie; Lin, Longnian; Hui, Lijian; Ma, Xueyun; et al.
Abstract: Optogenetic genome engineering is a powerful technology for high‐resolution spatiotemporal genetic manipulation, especially for in vivo studies. It is difficult to generate stable transgenic animals carrying a tightly regulated optogenetic system, as its long‐term expression induces high background activity. Here, the generation of an enhanced photoactivatable Cre recombinase (ePA‐Cre) transgenic mouse strain with stringent light responsiveness and high recombination efficiency is reported. Through serial optimization, ePA‐Cre is developed to generate a transgenic mouse line that exhibits 175‐fold induction upon illumination. Efficient light‐dependent recombination is detected in embryos and various adult tissues of ePA‐Cre mice crossed with the Ai14 tdTomato reporter. Importantly, no significant background Cre activity is detected in the tested tissues except the skin. Moreover, efficient light‐inducible cell ablation is achieved in ePA‐Cre mice crossed with Rosa26‐LSL‐DTA mice. In conclusion, ePA‐Cre mice offer a tightly inducible, highly efficient, and spatiotemporal‐specific genome engineering tool for multiple applications. Abstract : In this study, the generation of an enhanced photoactivatable Cre recombinase (ePA‐Cre) transgenic mouse strain which enables stringent light‐induced cell depletion and genome manipulation is reported. The superior stringency of the ePA‐Cre mouse makes the model a powerful tool for efficient, spatiotemporal, highly tunable, and noninvasive genome engineering for further biological applications.